2020
DOI: 10.1097/sap.0000000000002513
|View full text |Cite
|
Sign up to set email alerts
|

Ranking United States Plastic Surgery Residency Programs Based on Academic Achievement of Faculty Members

Abstract: Introduction The Doximity Residency Navigator is currently the only resource that ranks plastic surgery residency programs. Given the paucity of objective program rankings, in this study, we devised a new algorithm to rank plastic surgery programs based on academic achievement of faculty members. Methods The Fellowship and Residency Electronic Interactive Database was used to obtain the following information on plastic surgery programs: the amount of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
4
13
0
Order By: Relevance
“…Students who attend medical schools with smaller plastic surgery divisions with less or even no NIH funding have fewer research mentors and less financial support, making research opportunities less accessible. In fact, ranking surgical residency programs by NIH funding as a proxy for research activity has been suggested in the literature 14,17 . Supporting this hypothesis, Roy et al 6 found a positive correlation between publication numbers and institution NIH funding, and our study demonstrates that having greater plastic surgery NIH funding independently increases one's odds of presenting at least 3 times by more than 3-fold.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Students who attend medical schools with smaller plastic surgery divisions with less or even no NIH funding have fewer research mentors and less financial support, making research opportunities less accessible. In fact, ranking surgical residency programs by NIH funding as a proxy for research activity has been suggested in the literature 14,17 . Supporting this hypothesis, Roy et al 6 found a positive correlation between publication numbers and institution NIH funding, and our study demonstrates that having greater plastic surgery NIH funding independently increases one's odds of presenting at least 3 times by more than 3-fold.…”
Section: Discussionsupporting
confidence: 83%
“…In fact, ranking surgical residency programs by NIH funding as a proxy for research activity has been suggested in the literature. 14,17 Supporting this hypothesis, Roy et al 6 found a positive correlation between publication numbers and institution NIH funding, and our study demonstrates that having greater plastic surgery NIH funding independently increases one's odds of presenting at least 3 times by more than 3-fold. This disadvantage is further heightened for students without plastic surgery residency programs at their institutions.…”
Section: |supporting
confidence: 81%
See 2 more Smart Citations
“…8 Those residency programs that do have research years may not always have adequate teaching of academic skills or plastic surgery faculty mentors who have records of academic and funding success. 9 Institutions, research sponsors, and clinical leaders need to align the academic goals of the residents and faculty members with their professional responsibilities and measures of success. Progress in meeting one's academic goals needs to be assessed longitudinally, and adequate resources need to be committed to help the resident or faculty reach their academic Plastic and Reconstructive Surgery • February 2022 goals.…”
mentioning
confidence: 99%